Development of a Sensitive Methodology for the Analysis of Chlorobenzenes in Water Samples by Combination of Homogeneous Liquid‐liquid Microextraction via Flotation Assistance and Gas Chromatography‐flame Ionization Detection. Issue 12 (27th August 2014) - Khalilian, Faezeh; Rezaee, Mohammad
Abstract In this study, a simple, rapid and efficient method, homogeneous liquid‐liquid microextraction via flotation assistance (HLLME‐FA) combined with gas chromatography – flame ionization detection (GC‐FID), for the determination of chlorobenzenes (CBs) in water samples, has been described. In this research, a special extraction cell was designed to facilitate collection of the low‐density solvent extraction. No centrifugation was required in this procedure. The water sample solution was added into the extraction cell which contained an appropriate mixture of extraction and homogeneous solvents. By using air flotation, the organic solvent was collected at the conical part of the designed cell. Parameters affecting extraction efficiency were investigated and optimized. Under the optimum conditions, the detection limits, the precisions and the linearity of the method were found in the range of 0.2 to 1.5 µg L‐1, 5.7–9.3% (RSD, n =5) and 0.5–200 µg L‐1, respectively.